Non classic presentations of a genetic mutation typically associated with transient neonatal diabetes. (26th February 2020) - Devaraja, Janani; Elder, Charlotte; Scott, Adrian
Abstract : Summary: This case report describes a family pedigree of a mother and her children with an E227K mutation in the KCNJ11 gene. People with this particular gene mutation typically present with transient neonatal diabetes; with more than half the cohort relapsing into permanent diabetes in adolescence or early adulthood. However, the mother developed diabetes as an adolescent and thus was initially diagnosed as having Type 1 Diabetes. All her children have inherited the same genetic mutation but with differing presentations. Her second, third and fourth child presented with transient neonatal diabetes which remitted at varying times. Her first child is 16 years old but had not developed diabetes at the time of writing. The KCNJ11 gene codes for the KIR6.2 subunit of the KATP channels of the pancreatic beta cells. Mutations in this gene limit insulin release from beta cells despite high blood glucose concentrations. Most people with diabetes caused by this genetic mutation can be successfully managed with glibenclamide. Learning of the genetic mutation changed the therapeutic approach to the mother's diabetes and enabled rapid diagnosis for her children. Through this family, we identified that an identical genetic mutation does not necessarily lead to the same diabetic phenotype. We recommend clinicians to consider screening for this gene in their patients whom MODY is suspected; especially in those presenting before the age of 25 who remain C-peptide positive. Learning points: KATP channel closure in pancreatic beta cells is a critical step in stimulating insulin release. Mutations in the KIR6.2 subunit can result in the KATP channels remaining open, limiting insulin release. People with KCNJ11 mutations may not present with neonatal diabetes as the age of presentation of diabetes can be highly variable. Most affected individuals can be treated successfully with glibenclamide, which closes the KATP channels via an independent mechanism. All first degree relatives of the index case should be offered genetic testing, including asymptomatic individuals. Offspring of affected individuals should be monitored for neonatal diabetes from birth. Affected individuals will require long-term follow-up as there is a high risk of recurrence in later life.